2022
DOI: 10.54112/bcsrj.v2022i1.105
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Heat Stress on Agro-Morphometric and Fiberrelated Traits in Indigenous Upland Cotton Genotypes Under Semi-Arid Conditions

Abstract: To understand the impact of heat stress on agro-morphological and fiber quality-related traits in cotton, nine locally developed cotton genotypes were grown under heat stress conditions (Late sowing) at the cotton research station, Bahawalpur. Genotypes were laid-out under randomized complete block design (RCBD) in triplicates, where plant to plant and bed to bed distance was maintained as 30 cm and 75 cm, respectively. Data was collected from selected, guarded plants for agronomic as well as fiber quality-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Moreover, variations among cotton strains for these parameters were non-significant in replications except for plant height, which showed highly significant diversity among cotton strains with respect to plant height. Similar findings were also reported by Aslam et al, 2022;Hussain et al, 2023a;Hussain et al, 2023b andYousaf et al, 2023 who revealed significant variations among cotton genotypes for similar/same traits under heat stress conditions. The correlation coefficient analysis was executed to understand the magnitude and direction of association between studied plant traits in upland cotton strains under heat stress conditions (Table 4).…”
Section: Analysis Of Variance (Anova)supporting
confidence: 90%
“…Moreover, variations among cotton strains for these parameters were non-significant in replications except for plant height, which showed highly significant diversity among cotton strains with respect to plant height. Similar findings were also reported by Aslam et al, 2022;Hussain et al, 2023a;Hussain et al, 2023b andYousaf et al, 2023 who revealed significant variations among cotton genotypes for similar/same traits under heat stress conditions. The correlation coefficient analysis was executed to understand the magnitude and direction of association between studied plant traits in upland cotton strains under heat stress conditions (Table 4).…”
Section: Analysis Of Variance (Anova)supporting
confidence: 90%
“…the analysis is applied by several scientists and found helpful in categorize crop genotypes based on their divergence, performance, and performance under specified environments. Several researchers used principal component and PC1/PC2 biplot analysis in categorising cotton genotypes under different circumstances and found it very useful in classifying the genotypes based on their performance , Aslam et al, 2022Zafar et al, 2022and Zafar et al, 2021.…”
Section: Discussionmentioning
confidence: 99%
“…The data for several plant traits, including plant populations per hectare (P. Pop), plant height (PH), nodes per plant (NP), monopods per plant (MP), sympods per plant (SP), bolls per plant (BP), CLCuV incidence percentage (CLCuV), net photosynthetic rate (Pn), transpiration rate (Tr), flavonoid (Flv), peroxidases (POD), superoxide dismutase (SOD), ginning out turn (GOT), staple length (SL), fiber strength (FS) and seed cotton yield (SCY). Moreover, the CLCuV incidence percentage (CLCuV) was determined according to the formula used by Aslam et al (2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insect pests, a scarcity of high-quality seeds, cotton diseases such as cotton leaf curl disease, heat and drought stress, labor-intensive harvesting, fluctuating cotton prices, and shifting cropping patterns are the most significant problems in the cotton zone. This review examines the current condition of production, cotton-based breeding techniques, germplasm development, mechanization, and significant production limits (Aslam et al, 2022;Fatima et al, 2022ab;Malik & Ahsan, 2016).…”
Section: Introductionmentioning
confidence: 99%